PENGEMBANGAN MEDIA BONEKA TANGAN TERHADAP KETERAMPILAN BERBICARA SISWA MELALUI PEMBELAJARAN ROLE PLAYING - Siti Marthiasari; Nana Hendracipta; Rina Yuliana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2020)
This study aims to develop learning media products for grade III elementary school students at SDN Bugel 3. This research uses the Research and Development (R&D) research method with Borg and Gall development procedures. The products produced from this research were hand puppet media. This Hand Puppet was developed into a two-character hand puppet in one puppet or called 'two in one' as a visitor. The subjects in this study were 31 students in grade III of SDN Bugel 3. Data collected in this study were validation of material experts, linguists, media experts and product trial data. From the data obtained, the media of this hand puppet get an average score of expert validation of 91% so that it gets the category "Very Eligible", and get an average score of response of 93% including the criteria of "Very Good". From the results of this study it can be concluded that the two character hand puppets developed are feasible and effective in learning and can be used through role playing to foster student speaking skills.